Associations between neighborhood social capital, oral health risk factors, and tooth decay among Medicaid-enrolled adolescents: A hypothesis-generating preliminary study - Courtney M. Hill; Lloyd A. Mancl; Richard M. Carpiano; Adam C. Carle; Marilynn Rothen; Kyle Crowder; Michael Yoo; Donald L. Chi (PLoS ONE, 2025)
Neighborhood-based social capital – defined as resources within neighborhood social networks – is a potential contributor to adolescent oral health, but mechanisms that link the two are not well elucidated. We evaluated the potential mediating role of neighborhood, household, and individual oral health risk factors in the neighborhood social capital-tooth decay relationship. We collected cross-sectional data from 331 Medicaid-enrolled adolescents (ages 12–18 years) and one of their caregivers from 73 census tracts (neighborhoods) in three counties in Oregon, U.S.A in 2015 and 2016. Medicaid is a public insurance program in the U.S. providing no-cost dental insurance to low-income children. We measured four neighborhood social capital constructs: social support, social leverage, informal social control, and neighborhood organization participation. Oral health risk factors included worrying about food money, poor access to vegetables and fruits, inconsistent family and oral health routines, and adolescent stress. The outcome was number of untreated decayed tooth surfaces. Causal mediation analyses with mixed effect models were used to examine associations. Neighborhoods with higher social support had a lower prevalence of worrying about food money (prevalence ratio [PR] 0.74;95% CI: 0.56, 0.96;p = .02) as did neighborhoods with higher informal social control (PR 0.75;95% CI:0.58, 0.97;p = .03). All oral health risk factors were strongly associated with untreated decayed tooth surfaces. No form of neighborhood social capital was significantly associated with tooth decay. Natural indirect effects of neighborhood social support and informal social control operating through worrying about food money were not statistically significant. Future longitudinal studies that include robust measures of neighborhood social capital and adequate sample sizes are needed to enable neighborhood-based interventions that promote adolescent oral health.